CONSIDERING INDIVIDUAL PSYCHOLOGICAL CHARACTERISTICS OF STUDENTS IN THE PROCESS OF VOCATIONAL GUIDANCE. (Universal International Scientific Journal, 2026)
This article analyzes the issues of career guidance of students in the educational process. It also highlights the psychological aspects of the career choice process and the need to take into account the characteristics of students' age when guiding them to a career.
Keywords: educational process, career guidance, career promotion, need, career choice